Assessment of one-year overall survival among stage III breast cancer patients - Darwito; Sari, Ika Puspita; Wijayana, Singgih; Mahardinata, Nur Azid; Anwar, Sumadi Lukman; Ridhayani, Firda (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: The results of a comprehensive diagnosis, combined with the individual's general state, establish the appropriate therapeutic care for breast cancer patients. These management disparities have an impact on clinical outcomes, which may influence patient survival. The evaluation process of breast cancer management is essential as a strategy to boost the therapy's effectiveness in the future year. Objectives: Assessing survival rate, one-year overall survival, among stage III breast cancer patients.Methods: An observational study was conducted comprising a retrospective cross-sectional study. Data collected retrospectively from the medical record followed a total sampling technique. This study included patients with breast cancer as a main diagnosis with or without comorbidities and aged ≥ 18 years when undergoing their first diagnosis. Moreover, the exclusion criteria were patients who had incomplete medical record data, undergoing breast cancer treatment at other healthcare facilities, unspecified clinical stage, and patients who had been diagnosed with non-stage III breast cancer. The survival time of the participants is defined as the number of months from initial diagnosis to their last status (alive, died, or loss of follow-up). One-year overall survival was projected using the Kaplan-Meier curve and presented as a percentage with a 95% confidence interval. Results: Of the 23 patients with stage III breast cancer and the mean age was 57.39 ± 10.417 years. The one-year overall survival for stage III breast cancer was 78.3%. In addition, metastases conditions were associated with worse one-year overall survival compared to patients without metastases (40.0% vs 88.9%, p=0.028).Conclusion: The survival rate of breast cancer patients remains lower than in another recent study from Indonesia. This indicates the requirement of treatment strategies evaluation.